(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2024)
This article draws inspiration from the ongoing debate on mutual aid, particularly its emergence as a community-based and led response during the Covid-19 pandemic. One perspective views mutual aid as a positive collective practice, effective for immediate, small-scale needs but inadequate for addressing large-scale systemic inequalities. Advocates of this view propose that mutual aid should operate under state guidance to complement centrally orchestrated responses to systemic issues. In contrast, the opposing side challenges this view, asserting that mutual aid is inherently an emancipatory practice. It aligns with the core principles of anarchism, including anti-capitalism, anti-statism, and anti-authoritarianism. Owing to this ideological alignment, these proponents argue that mutual aid should not be supplementary to the state; doing so would risk transforming it into a form of charity. This article aims to enrich the broader dialogue on mutual aid by introducing a dichotomous framework for its understanding. This framework categorises mutual aid into two distinct types: Organic mutual aid, which arises ’naturally’ from immediate communal needs but lacks the political impetus to confront hierarchical power structures. Political mutual aid, born out of political motivation with the objective of challenging both official and unofficial hierarchical power structures. To elucidate the necessity of this dichotomous framework in grasping mutual aid’s dual dimension, I will delve into both recent and past experiences of mutual aid in Greece. However, before advancing this proposal, it is essential to examine the underlying reasoning behind the two perspectives in this debate.